(untitled) (Research, Society and Development, 2022)
To assess the profile and causality of adverse events related to herbal medicines of widespread use in Brazil, we conducted an open, prospective, before-and-after clinical trial with patients at an outpatient clinic specialized in complementary and alternative medicine. Participants were submitted to laboratory tests prior to and after use of the medicines, as well as following a period of discontinuation in those experiencing adverse events. Occurrence of adverse events and their severity were verified in accordance with the WHO Toxicity Grading Scale for Determining the Severity of Adverse Events, and their causality established via the Naranjo algorithm. Forty-two subjects participated in the trial, of which 25 experienced grade 1 toxicity adverse events, mainly hyperamylasemia, and 14 continued to experience them following discontinuation, mainly hypomagnesemia. Mean/median values of laboratory tests performed in each phase were within specifications. Statistical analysis of these values in pre-treatment and treatment (n=42) and in treatment and post-treatment phases (n=22) showed statistical significance for activated partial thromboplastin time (p=0.020) in the first correlation. The Naranjo algorithm established a possible causal relationship between the use of herbal medicines and the adverse events reported. By signaling a low probability of occurrence, the algorithm indicates the safe use of these medicines under the experimental conditions employed.